Impact of Psychosocial Factors on Quality of Life: A Case Study of End Stage Renal Disease - Iqra Nazar; Dr. Fatima Kamran; Dr. Rafia Rafique; Dr. Ghulam Ishaq (Journal of Research in Social Sciences)
End-stage renal disease (ESRD) occurs when kidneys gradually lost its function. In Pakistan, the prevalence of ESRD is 37.9% of the adult population overall. This case study is describing how psychosocial factors have greater impact on client with ESRD, which ultimately influencing her overall quality of life (QoL). The client F.A was a 55 years old married female, diagnosed with ESRD due to Primary Hypertension and Type I Diabetes. Client was referred to trainee health psychologist for psychosocial assessment as a consequence of Hemodialysis. She was presented with the physical & psychological complaints such as fatigue due to low Hb level, muscles cramps and difficulty in breathing due to Myocardial Infraction (MI), irritability after diagnosis of ESRD, anger over little matters, automatic worrying thoughts regarding her condition and restlessness. An in-depth case history interview was carried out to gather information using both informal and formal assessments. 12 sessions have been conducted with the patient. These assessments covered all psychosocial aspects such as illness perception, health locus of control, health beliefs, perceived health status, perception of the doctor-patient relationship, perception of health care services, personality/life orientation, adherence (dietary, fluid, and medication), and QoL. The client found below average on QoL depicted through formal assessment and seemed to be non-adhere towards dietary habits, medication, and treatment of HCV or MI. In addition, she seemed to have negative illness perceptions, poor health status, maladaptive health beliefs, spiritual health locus of control and dissatisfied doctor-patient relationship. The intervention plan comprised of psychoeducation, cost and benefit analysis, coping statements, role playing technique, religious coping anger management, attention strategy technique, baseline chart and ABC model of Cognitive Behavioral Therapy (CBT). The intervention plan showed significant improvement in managing psychosocial targeted areas.